STRATEGI MANAJEMEN RESIKO PETANI CABAI MERAH PADA LAHAN SAWAH DATARAN RENDAH DI JAWA JAWA TENGAH - Saptana Saptana; Arief Daryanto; Heny K. Daryanto; Kuntjoro Kuntjoro (Jurnal Manajemen & Agribisnis, 2010)
Red pepper farmers as the farm managers deal with risk management. Objectives of this study was to analysis farmers’ behavior in coping with risks and risks management strategy on red pepper farm management on lowland in Central Java. This study was carried out between February to March, 2009, in lowland areas in Kersana sub district, Brebes district; Karangnongko, Jogonalan, Manisrenggo, and Ngawen sub districts, Klaten district, and Teras sub district, Boyolali district, Central Java.   Decision to adopt dominant cropping pattern by including red pepper as high economic value commodity was an ex ante risk management strategy. Meanwhile, interactive risk management was carried out through over use of seeds and pesticides. If the farms failed and led to lower households’ incomes and farm sustainability, the farmers tended to employ other farm incomes, to draw savings, to sell some assets, and to borrow as the ex post risk strategy management. Implications of this study are: (i) cropping patterns need to include red pepper to sustain and to improve farmers’ incomes; (ii) application of hybrid red pepper varieties to cope with environmental pressure and pests’ attack; (iii) farm practice technique should be locally specific based on red pepper varieties and agro ecology; (iv) farm diversification and agriculture insurance could lessen production risk; and (v) farmers’ group and contract farming will reduce marketing risks.